Enhancing mobile shopping experience using QR code: an exploratory study / Suzana Zambri …[et al.] - Zambri, Suzana; Hasani, Siti Aishah; Abdul Aziz, Maslina; Daud, Nor Aziah; Noordin, Nurulhuda; Hasssan, Syahida (Universiti Teknologi MARA, 2021)
Quick Response (QR) codes are increasingly visible in various fields. With advances in QR code, mobile shopping is becoming one of the most important channels in the retail industries. The aims of this research are to discover the willingness of the Malaysian university community to use QR codes in the buying process using smartphones as well as their perception about the functionality and usefulness of QR Codes. Through review of literature and responses from interviews, the article firstly clarified the characteristics and applicability of the QR Codes, especially in retail. This research applied design thinking methodology that provides a solutionbased approach to solving problems. It is found that the use of smartphones and QR codes for mobile shopping has become increasingly popular and has enhanced users’ shopping experience. Users can easily purchase products by engaging in mobile shopping. Review function can be added to this mobile application which enables users to write their shopping experience for business owners to improve their services. This is a pioneering work for Malaysian literature, as there are limited studies that have explored issues concerning the use of QR codes in the mobile buying process.